Glioblastoma Recurrence Correlates With Increased APE1 and Polarization Toward an Immuno-Suppressive Microenvironment - Hudson, Amanda L.; Parker, Nicole R.; Khong, Peter; Parkinson, Jonathon F.; Dwight, Trisha; Ikin, Rowan J.; Zhu, Ying; Chen, Jason; Wheeler, Helen R.; Howell, Viive M. (Frontiers in Oncology, 2018)
While treatment with surgery, radiotherapy and/or chemotherapy may prolong life for patients with glioblastoma, recurrence is inevitable. What is still being discovered is how much these treatments and recurrence of disease affect the molecular profiles of these tumours and how these tumours adapt to withstand these treatment pressures. Understanding such changes will uncover pathways used by the tumour to evade destruction and will elucidate new targets for treatment development. Nineteen matched pre-treatment and post-treatment glioblastoma tumours were subjected to gene expression profiling (Fluidigm, TaqMan assays), MGMT promoter methylation analysis (pyrosequencing) and protein expression analysis of the DNA repair pathways, known to be involved in temozolomide resistance (immunohistochemistry). Gene expression profiling to molecularly subtype tumours revealed that 26% of recurrent post-treatment specimens did not match their primary diagnostic specimen subtype. Post-treatment specimens had molecular changes which correlated with known resistance mechanisms including increased expression of APEX1 (p<0.05) and altered MGMT methylation status. In addition, genes associated with immune suppression, invasion and aggression (GPNMB, CCL5 and KLRC1) and polarisation towards an M2 phenotype (CD163 and MSR1) were up-regulated in post-treatment tumours, demonstrating an overall change in the tumour microenvironment favouring aggressive tumour growth and disease recurrence. This was confirmed by in vitro studies that determined that glioma cell migration was enhanced in the presence of M2 polarised macrophage conditioned media. Further, M2 macrophage-modulated migration was markedly enhanced in post-treatment (temozolomide resistant) glioma cells. These findings highlight the ability of glioblastomas to evade not only the toxic onslaught of therapy but also to evade the immune system suggesting that immune-altering therapies may be of value in treating this terrible disease.